Visual control of trunk translation and orientation during locomotion - Anson, E.; Agada, P.; Kiemel, T.; Ivanenko, Y.; Lacquaniti, F.; Jeka, J. (Experimental brain research, 2014)
Previous studies have suggested distinct control of gait characteristics in the anterior–posterior (AP) and medial–lateral (ML) directions in response to visual input. Responses were larger to a ML visual stimulus, suggesting that vision plays a larger role in stabilizing gait in the ML direction. Here, we investigated responses of the trunk during locomotion to determine whether a similar direction dependence is observed. We hypothesized that translation of the trunk would show a similar ML dependence on vision, but that angular deviations of the trunk would show equivalent responses in all directions. Subjects stood or walked on a treadmill at 5 km/h while viewing a virtual wall of white triangles that moved in either the AP or ML direction according to a broadband input stimulus. Frequency response functions between the visual scene motion and trunk kinematics revealed that trunk translation gain was larger across all frequencies during walking compared with standing. Trunk orientation responses were not different from standing at very low frequencies; however, at high frequencies, trunk orientation gain was much higher during walking. Larger gains in response to ML visual scene motion were found for all trunk movements. Higher gains in the ML direction while walking suggest that visual feedback may contribute more to the stability of trunk movements in the ML direction. Vision modified trunk movement behavior on both a slow (translation) and fast (orientation) time scale suggesting a priority for minimizing angular deviations of the trunk. Overall, trunk responses to visual input were consistent with the theme that control of locomotion requires higher-level sensory input to maintain stability in the ML direction.